2007
DOI: 10.2169/internalmedicine.46.6152
|View full text |Cite
|
Sign up to set email alerts
|

Change of the Image of the Posterior Pituitary in a Patient with Mineralocorticoid-responsive Hyponatremia of the Elderly:Comparison of Findings before and after Treatment

Abstract: F i g u r e 1 . Cr a n i a l ma g n e t i c r e s o n a n c e i ma g i n g ( MRI ) d e mo n s t r a t e d a n a b s e n c e o f h i g h i n t e n s i t y o f t h e p o s t e r i o r p i t u i t a r y o n T 1 -we i g h t e d i ma g e s ( F i g 1 A) . Af t e r n o r ma l i z a t i o n o f t h e s e r u m s od i u m l e v e l a n d p l a s ma o s mo l a l i t y , h i g h i n t e n s i t y o f t h e p o s t e r i o r p i t u i t a r y o n T 1 -we i g h t e d i ma g e s wa s i mp r o v e d ( F i g 1 B ) . SHORT CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…[9] Serum ADH levels were over the detectable concentration in 26 patients despite hyponatremia and its median is 0.9 pg/mL. [5,7,9–13,15] Water restriction test was performed among 7 patients in 5 reports to differentiate them from SIAD. [5,7,12,14,15] Hyponatremia in these 7 cases was exacerbated by the test.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Serum ADH levels were over the detectable concentration in 26 patients despite hyponatremia and its median is 0.9 pg/mL. [5,7,9–13,15] Water restriction test was performed among 7 patients in 5 reports to differentiate them from SIAD. [5,7,12,14,15] Hyponatremia in these 7 cases was exacerbated by the test.…”
Section: Resultsmentioning
confidence: 99%
“…Fludrocortisone is a mineralocorticoid that promotes sodium reabsorption in the distal renal tubule. These effects may occur in cases of mineralocorticoid-responsive hyponatremia of the elderly (MRHE) ( 13 ), SIADH, and heart failure. Therefore, fludrocortisone administration may not be a diagnostic treatment for MRHE.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of mineralocorticoid-responsive hyponatremia of the elderly (MRHE) with unknown etiology is proposed in two reports. 11,12 In these reports, it is reported that the administration of fludrocortisone possesses benefit for the treatment of hyponatremia in the elderly. It is possible that fludrocortisones could have been used in all five of our cases.…”
Section: Discussionmentioning
confidence: 99%